Crisis Management: Government Strategy in Framing Reform Proposals and Communications. Issue 2 (3rd April 2018) - Cwalina, Wojciech; Falkowski, Andrzej
Abstract : One of the key determinants of the popularity of politicians is keeping election pledges, which promises voters' satisfaction and ensures their backing for those in power. Economic slowdowns and social and political crises are the most challenging periods in terms of retaining or boosting popularity. To face up to such dire circumstances, authorities seek to pass through drastic reforms affecting either all or some selected groups of voters. Based on Polish examples, the empirical studies presented herein demonstrate such strategies of governance and the creation of such electoral political messages that help maintain the popularity of the government or, at least, materially alleviate the negative consequences of introduced, yet unpopular reforms. The strategies rest upon regularities derived from the prospect theory concerning the linking of negative events in the minimizing of dissatisfaction and the separation of positive events in the maximizing of satisfaction. The investigated hypothesis covers the internal consistency of different but negative information about unpopular reforms. For it is not enough to combine negative events with a view to reducing the negative emotions in political messages. The effect of such a reduction will only be guaranteed when the linked events are perceived as consistent by voters.